F.1 Maths Question

1a)Simplify (p2 -4pq+q2) - (p2+4pq-q2)

1b)Hence, find the value of the above expression when p=2 and q= -3.

1 個解答

評分
  • 1 十年前
    最愛解答

    1a)Simplify (p² -4pq+q²) - (p²+4pq-q²)

    (p² -4pq+q²) - (p²+4pq-q²)

    =p² -4pq+q²-p²-4pq+q²

    = -8pq+2q²

    1b)Hence, find the value of the above expression when p=2 and q= -3.

    -8pq+2q²

    =-8(2)(-3)+2(2)²

    =48+8

    =56

    2007-06-12 21:13:29 補充:

    sorry,part b錯了。更正:1b)Hence, find the value of the above expression when p=2 and q= -3.-8pq+2q²=-8(2)(-3)+2(-3)²=48+18=66

還有問題嗎?立即提問即可得到解答。